Next-to-leading order QCD corrections to electroweak Zjj production in the POWHEG BOX - Jaeger, B; Schneider, S; Zanderighi, G (2012)
We present an implementation of electroweak Z-boson production in association with two jets at hadron colliders in the POWHEG framework, a method that allows the interfacing of NLO-QCD calculations with parton-shower Monte Carlo programs. We focus on the leptonic decays of the weak gauge boson, and take photonic and non-resonant contributions to the matrix elements fully into account. We provide results for observables of particular importance for the suppression of QCD backgrounds to vector-boson fusion processes by means of central-jet-veto techniques. While parton-shower effects are small for most observables associated with the two hardest jets, they can be more pronounced for distributions that are employed in central-jet-veto studies. © SISSA 2012.